2016
DOI: 10.1101/054015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Prediction of Hybrid Combinations in the Early Stages of a Maize Hybrid Breeding Pipeline

Abstract: Prediction of single-cross hybrid performance has been a major goal of plant breeders since the beginning of hybrid breeding. Genomic prediction has shown to be a promising approach, but only limited studies have examined the accuracy of predicting single cross performance. Most of the studies rather focused on predicting top cross performance using single tester to determine the inbred parent’s worth in hybrid combinations. Moreover, no studies have examined the potential of predicting single crosses made amo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…These small SCA variances explain why incorporating SCA effects into the prediction models did not further improve predictive abilities (Table S1 in File S2), similar to what was observed by Westhues et al (2017) in a related dataset for silage maize. In contrast, distinctly larger ratios of SCA to GCA variance were reported by Bernardo (1996) and Kadam et al (2016), where the latter study comprised materials originating exclusively from several North American Dent heterotic groups. Heritabilites on an entry-mean basis corresponded well to estimates published by Massman et al (2013), who reported 0.85 for GY and 0.98 for grain moisture among maize singlecrosses.…”
Section: Foundation Of Hybrid Predictionmentioning
confidence: 67%
See 1 more Smart Citation
“…These small SCA variances explain why incorporating SCA effects into the prediction models did not further improve predictive abilities (Table S1 in File S2), similar to what was observed by Westhues et al (2017) in a related dataset for silage maize. In contrast, distinctly larger ratios of SCA to GCA variance were reported by Bernardo (1996) and Kadam et al (2016), where the latter study comprised materials originating exclusively from several North American Dent heterotic groups. Heritabilites on an entry-mean basis corresponded well to estimates published by Massman et al (2013), who reported 0.85 for GY and 0.98 for grain moisture among maize singlecrosses.…”
Section: Foundation Of Hybrid Predictionmentioning
confidence: 67%
“…2013; Technow et al 2014;Kadam et al 2016). Traditionally, pedigree and genomic information on the parent lines have been used for predictions of breeding values, and the majority of studies in the past decade focused on conceiving and improving algorithms for exploiting the full potential of these data (Meuwissen et al 2001;Maenhout et al 2010;Habier et al 2011).…”
mentioning
confidence: 99%
“…Because of the complexities of the environment, which include climate, soil condition, and crop management practices, one of the most difficult aspects of predicting crop yield is applying appropriate models including climatic and phenotypic data and molecular markers (Kadam et al, 2016). Climatic and phenotypic data can be easily recorded with automatic instruments; however, they often fluctuate significantly.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…Thus, there is not a conventional value used in all species. For example, in maize 21 and wheat, 22 a MAF of 0.05 was used for GBS and an Infinitum SNP array, respectively, while 23 considered a cut-off of 0.01 in wheat for GBS data. PMMS is the percentage of missing marker scores is the percentage of marker scores in the genomic data set that are missing.…”
Section: Qc Of the Genomic Datamentioning
confidence: 99%